The guilty - Baldacci, David (New York : Grand Central Publishing, 2015)
When his father is charged with murder and refuses to do anything to prove his innocence, Will Robie returns as an outsider to his hometown of Cantrell, Mississippi--where is he is met with distrust--to conduct his own investigation.
Keywords: Assassins -- Fiction; Murder -- Investigation -- Fiction; Adult children -- Fiction; Fathers and sons -- Fiction; Large type books; Mississippi -- Fiction; Suspense fiction